Identification of Target Golimumab Levels in Maintenance Therapy of Crohn's Disease and Ulcerative Colitis Associated With Mucosal Healing. Issue 5 (17th September 2019) - Boland, Karen; Greener, Tomer; Kabakchiev, Boyko; Stempak, Joanne; Tessolini, Jenna; Li, Rachelle; Soriano, Joelle; Croitoru, Kenneth; Nguyen, Geoffrey; Steinhart, A Hillary; Weizman, Adam V; Silverberg, Mark S
Abstract: Introduction: Golimumab is approved as a therapy for ulcerative colitis (UC) patients. Recent data also demonstrate efficacy in Crohn's disease (CD); however, little is known about target drug levels to achieve endoscopic remission. Methods: We performed a retrospective analysis of IBD patients on maintenance golimumab. Median trough levels were compared using Kruskal-Wallis test, and logistic regression was used to construct a probabilistic model to determine sensitivity and specificity of levels predicting mucosal healing. Results: Fifty-eight patients on maintenance golimumab were included (n = 39 CD, n = 19 UC/IBD-unclassified [IBDU]). Forty percent (n = 23) were cotreated with an immunomodulator, 95% (n = 55) of patients were anti-TNF experienced, and 15.5% (n = 9) had 3 or more prior biologic therapies. Forty-four percent of patients achieved mucosal healing with endoscopic response in a further 26% of patients. Clinical remission was recorded in 41% of patients, and 82% had clinical response. Patients were treated with doses generally higher than the approved maintenance dose. In CD patients, median golimumab trough levels were higher in patients with mucosal healing (8.8 μg/mL vs 5.08 μg/mL, P = 0.03). After calculation of a receiver operating characteristic (ROC) curve for mucosal healing vs nonresponse, a trough level >8 μg/mL was associated with mucosal healing, with 67% sensitivity, 88% specificity, and a likelihood ratio of 3:4. Conclusion: Treatment with golimumab was associated with mucosal healing in 44% of all IBD patients. Higher golimumab levels were associated with mucosal healing in CD. These findings support the need for prospective studies to determine target golimumab levels in IBD, which may impact current clinical practices in relation to selection of maintenance dosing. Abstract : Recent data have outlined the potential of golimumab to achieve mucosal healing in Crohn's disease and ulcerative colitis, but drug monitoring targets are lacking. We have identified golimumab trough levels associated with mucosal healing in a largely anti-TNF experienced patient population.